2015
DOI: 10.1021/acs.jafc.5b01584
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Configurations and NO Inhibitory Activities of Terpenoids from Curcuma longa

Abstract: Curcuma longa L., belonging to the Zingiberaceae family, is a perennial herb and has been used as a spice and a pigment in the food industry. In the ongoing search for inhibitory reagents of NO production and survey of the chemical composition of natural vegetable foods, the chemical constituents of C. longa used as spice were investigated. This investigation resulted in the isolation of 2 new terpenoids and 14 known analogues. Their structures were established on the basis of the extensive analyses of 1D and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 37 publications
0
36
0
1
Order By: Relevance
“…Second, Somchit et al showed that a curcumanoid from C. longa inhibits the NO signaling pathway in inflamed human intestinal CaCo cells ( Somchit et al, 2014 ). Third, Xu et al showed that terpenoids from a C. longa extract inhibited the NO production by murine LPS-primed microglial BV2 cells ( Xu et al, 2015 ). Thus, C. longa may block the LPS-triggered HMGB1 release of macrophages by inhibiting NO-associated cellular signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, Somchit et al showed that a curcumanoid from C. longa inhibits the NO signaling pathway in inflamed human intestinal CaCo cells ( Somchit et al, 2014 ). Third, Xu et al showed that terpenoids from a C. longa extract inhibited the NO production by murine LPS-primed microglial BV2 cells ( Xu et al, 2015 ). Thus, C. longa may block the LPS-triggered HMGB1 release of macrophages by inhibiting NO-associated cellular signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when normal murine splenocytes are treated with the polysaccharide fraction of C. longa extract, their LPS-stimulated release of prostaglandin E2 and interleukin-12 is potently inhibited ( Sengupta, Sharma & Chakraborty, 2011 ). Furthermore, when LPS-stimulated murine microglial BV-2 cells and inflamed human intestinal Caco-2 cells are treated with a curcumanoid and terpenoids from a C. longa extract, respectively, their inflammation improves markedly: this is achieved by regulation of the nitric oxide (NO) signaling pathway ( Somchit et al, 2014 ; Xu et al, 2015 ). In addition, the ethyl acetate fraction of C. longa exhibits strong scavenging activity for peroxynitrite, which is a cytotoxic intermediate that is generated by a reaction between NO and superoxide anion ( Kim et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…2016 ; Ma and Gang 2006 ; Park and Kim 2002 ; Xu et al. 2015 ), and few studies were conducted on the chloroplast genome of C. longa . In this study, we obtained the complete chloroplast genome sequence of C. longa by Illumina and PacBio sequencing technologies.…”
mentioning
confidence: 99%
“…Since the Japanese scientific academic community defined the class of "functional foods"— conventional and modified foods that included additional health benefits beyond basic nutrition in the early 1980s, the foods with health benefits became more and more popular in the daily diets of individuals [ 1 ]. Turmeric, powder of Curcuma longa L. rhizome (Zingiberaceae), is widely used as a food additive (for its flavor and yellow color), dietary supplement, and medicine [ 2 , 3 ]. It is officially documented as a medicine and food dual purposes items by the National Health Commission of the People’s Republic of China [ 4 ] and as Dietary Supplement by the United States Pharmacopeia (USP) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%